Radiation dose reduction in CT with adaptive statistical iterative reconstruction (ASIR) for patients with bronchial carcinoma and intrapulmonary metastases. Issue 5 (May 2016) - Schäfer, M.-L.; Lüdemann, L.; Böning, G.; Kahn, J.; Fuchs, S.; Hamm, B.; Streitparth, F.
Abstract : Aim: To compare the radiation dose and image quality of 64-row chest computed tomography (CT) in patients with bronchial carcinoma or intrapulmonary metastases using full-dose CT reconstructed with filtered back projection (FBP) at baseline and reduced dose with 40% adaptive statistical iterative reconstruction (ASIR) at follow-up. Materials and methods: The chest CT images of patients who underwent FBP and ASIR studies were reviewed. Dose–length products (DLP), effective dose, and size-specific dose estimates (SSDEs) were obtained. Image quality was analysed quantitatively by signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) measurement. In addition, image quality was assessed by two blinded radiologists evaluating images for noise, contrast, artefacts, visibility of small structures, and diagnostic acceptability using a five-point scale. Results: The ASIR studies showed 36% reduction in effective dose compared with the FBP studies. The qualitative and quantitative image quality was good to excellent in both protocols, without significant differences. There were also no significant differences for SNR except for the SNR of lung surrounding the tumour (FBP: 35±17, ASIR: 39±22). Discussion: A protocol with 40% ASIR can provide approximately 36% dose reduction in chest CT of patients with bronchial carcinoma or intrapulmonary metastases while maintaining excellent image quality. Highlights: adaptive statistical iterative reconstruction in chest computed tomography scans. patients with bronchial carcinoma or intrapulmonary metastases. ASIR studies showed 36% reduction in effective dose compared with the FBP studies. the qualitative and quantitative image quality was good to excellent in both protocols.